Health behavior of young patients with ischemic stroke in Estonia: A score of five factors - Minni Saapar; Riina Vibo; Siim Schneider; Liisa Kõrv; Sandra Mallene; Janika Kõrv (Brain and Behavior, 2023)
Abstract Background Behavioral risk factors are common among young patients with stroke. This study aimed to compare the health behavior of patients and healthy controls and develop a combined risk score of health behavior. Methods The health behavior of patients aged 18–54 years who suffered an ischemic stroke from 2013 to 2020 in Estonia was compared to the Health Behavior among Estonian Adult Population 2014 study sample. We chose five risk factors for comparison: smoking status, body mass index, physical exercise, diet (salt use and vegetable consumption), alcohol intake (quantity and frequency), and composed a summary score. Results Comparing 342 patients and 1789 controls, daily smoking (49.0% vs. 22.7%), obesity (33.4% vs. 15.9%), low physical activity (< twice/week) (72.2% vs. 60.5%), excessive salt use (8.6% vs. 4.5%), and frequent alcohol use (≥ weekly) (39.9% vs. 34.0%) were more prevalent among patients. The differences in infrequent vegetable consumption (<6 days/week) and excessive alcohol consumption (7 days, >8 units/females, >16 units/males) were not significant. The observed differences were similar for age groups 18–44 years and 45–54 years. The average Health Behavior Stroke Risk Score (0–10) was 4.6 points (CI 4.4–4.8, SD ± 1.97) for patients and 3.5 points (CI 3.4–3.6, SD ± 1.90) for controls. Conclusions Before stroke, young patients displayed significantly worse health behavior than the general population. The largest differences were found for smoking and obesity, and a cumulation of risk factors was observed via the HBSR score.